Program Arsip Vital di Kementrian Agama Jakarta Selatan - Muthia Safitri; Trisni Handayani (Jurnal Utilitas, 2016)
Research intended to describe Vital Archive Program of Staffing Department of Ministry of Religious Affair of Southern Jakarta Municipality. The method used was qualitative descriptive. Sampling method used was purposive sampling technique. The research informants’ purposively chosen from the staffs. The data acquired through interviews, document analysis, and participant observation. Data validated through triangulation techniques. The research revealed that Vital Archive Program of Staffing Department of Ministry of Religious Affair conducted by simple technique including protection, maintenance, damage prevention, and safekeeping of vital archive. The research protection process implemented by vital archive dispersal, duplication, and saving program. The research recommends the office to pay attention to the dispersal and storage of vital archive. So, the archive management runs better.